Efforts to Overcome Juridical Constraints in Countering Terrorism in Indonesia by The Indonesian National Armed Forces - Arief Fahmi Lubis (Syntax Corporation Indonesia, 2022)
The description of acts of terrorism as a crime against the state is a serious threat to the sovereignty of each country. Acts of terrorism in Indonesia can now be qualified as military threats, namely threats using organized armed forces, which are considered to have capabilities that endanger the state's sovereignty, the territorial integrity of the country, and the safety of the entire nation. The TNI's (Indonesian National Armed Forced) efforts to overcome obstacles in dealing with terrorism in Indonesia are carried out under the Government Regulation in the lie of Law in dealing with it. Through the role of the TNI that is shown to the community and government, showing that the TNI carries out the rights and obligations according to its position, it carries out a function. From looking at these roles, we can illustrate that roles can also be interpreted as individual behavior, which is important for the social structure of society because social beings tend to live in groups. Also, empirical juridical research, namely conducting studies based on observations of the handling of acts of terrorism in Indonesia involving the TNI. It can be concluded that TNI institutions can be used as material for consideration in authority to deal with acts of terrorism.